1985
DOI: 10.1111/j.1471-0528.1985.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral clonidine on human cardiovascular responsiveness: a possible explanation of the therapeutic action of the drug in menopausal flushing and migraine

Abstract: The effect of an alpha-adrenergic agonist. clonidine hydrochloride, on cardiovascular responses to noradrenaline, adrenaline and angiotensin was investigated in menopausal women with hot flushes. The increase in forearm blood flow induced by adrenaline, noradrenaline or angiotensin was significantly less in women treated for at least 6 weeks with clonidine compared with that induced in the women by infusions given before treatment. Pulse rate during the amine infusions was significantly lower after clonidine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Ginsburg et al, found that an increase in forearm blood flow induced by intravenous infusion of adrenaline, angiotensin and noradrenaline was significantly less in women treated for at least 6 weeks with clonidine compared with that induced in the women by infusions given before treatment. (36). However, our results would seem to contradict these.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Ginsburg et al, found that an increase in forearm blood flow induced by intravenous infusion of adrenaline, angiotensin and noradrenaline was significantly less in women treated for at least 6 weeks with clonidine compared with that induced in the women by infusions given before treatment. (36). However, our results would seem to contradict these.…”
Section: Discussioncontrasting
confidence: 55%
“…It has also been shown to have a beneficial effect on menopausal flushing (13)(14)(15), in particular by decreasing the intensity of the flushes. The mechanism is not fully understood, however it may exert its effect on hot flushing through a reduction in peripheral vascular reactivity (16) and also through central mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…44,45,46,47 Our results seem to indicate that the therapeutic effort should be oriented towards a partial "blockade" of the sympathetic instability, most probably in its function of vasomotor control. 43 Based on our present study, different pharmacologic agents (alpha-, beta-and calcium blockers, etc...) can be tested as to their efficacy in reducing both the autonomic imbalance related to migraine, and the occurrence of migraine attack.…”
Section: Discussionmentioning
confidence: 68%
“…43 Based on our present study, different pharmacologic agents (alpha-, beta-and calcium blockers, etc...) can be tested as to their efficacy in reducing both the autonomic imbalance related to migraine, and the occurrence of migraine attack. 44,45,46,47 Our results seem to indicate that the therapeutic effort should be oriented towards a partial "blockade" of the sympathetic instability, most probably in its function of vasomotor control.…”
Section: Discussionmentioning
confidence: 68%
“…It has not yet been ruled out, whether the effect of clonidine is dependent on the dosage. Ginsburg et al [20] did postulate that there will be no difference between 0.1 versus 0.15 mg whereas Laufer et al [13] could demonstrate a dose-dependent effect of clonidine from 0.1 to 0.2, and 0.4 mg per day. Instead of using venlafaxine extended release 75 mg per day, we used 37.5 mg twice a day to provide two tablets with treatment in both groups instead of a placebo in the venlafaxine group.…”
Section: Discussionmentioning
confidence: 99%